Risk of depression in patients with chronic rhinosinusitis: A nationwide population-based retrospective cohort study - Che Lun Hsu (2018)
© 2016 Elsevier B.V. Background Depression is prevalent in patients with chronic rhinosinusitis (CRS). However, no population-based study has ever investigated this relationship. We used nationwide population insurance data to conduct a retrospective cohort study to evaluate the subsequent risk of depression among patients with CRS. Methods We used the National Health Insurance Research Database (NHIRD) of Taiwan identified 15,371 CRS patients diagnosed during 2000–2010. The non-CRS group consisted of 61,484 individuals without CRS frequency matched by sex, age, and the year of diagnosis. The occurrence of depression was monitored until the end of 2011. The hazard ratios (HRs) of depression were estimated using the Cox proportional hazards model after adjusting for demographic characteristics and comorbidities. Results The overall incidence of depression was 77% higher in the CRS group than in the non-CRS group (8.25 vs. 4.66/1000 person-years, p<0.001), with an adjusted HR of 1.56 (95% confidence interval=1.43–1.70). Further data analyses revealed that the adjusted HRs of depression in the CRS group compared with the non-CRS group by sex, age, urbanization level, monthly income, occupation category, and comorbidity were all significant. However, there was no difference in incidences of depression between CRS patients with and without surgical treatment (8.31 vs. 8.24/1000 person-years). Conclusion The present study suggests that patients with CRS are at an increased risk of depression, compared with those without CRS. Therefore, we should pay attention to the psychiatric status of these patients and provide adequate support for them.